Perceived health status among middle-aged Polish people in relation to selected demographic and social factors - Kaczmarek, Maria; Skrzypczak, Magdalena (Anthropological Review, 2012)
Self-rated health is an important measure of health status and outcomes and plays a significant role in the quality of life. The main purpose of the study was to estimate selected demographic and socio-economic factors associated with perceived health status among middle-aged Polish people. The sample being studied consisted of 5,776 women and 2,191 men aged 35–65 years, participants of two nation-wide cross-sectional surveys: the survey on middle-aged women’s health and quality of life (WOMID) and the survey on men’s health and quality of life, both conducted in 2000–2004. Participants were administered a gender-specific questionnaire on demographic, socio-economic status, lifestyle behaviours and self-rated health. The subjectively evaluated health status was then correlated with sex, age, marital status, place of residence, education level, financial situation, types of leisure time and the tobacco use. Data were processed using uni- and multivariate statistical procedures including the logistic regression models LOGITs and multiple correspondence analysis (MCA). It was found that the perceived health status was associated with women’s and men’s age, and in women with their menopausal status. Women were likely to evaluate their health significantly worse than men. It was found that marital status, educational attainment and financial well-off were the factors significantly associated with perceived health status in both women and men. In concluding remarks it should be stated that the health perception of women and men in mid-life is significantly related to their socio-economic status.